Institutional Hybridity in Networked Cultural Organizations through Boundary Work - Haapakorpi, Arja; Kolehmainen, Jari; Jousmäki, Henna; Leinonen, Minna; Siirtola, Emmi (Nordic Journal of Working Life Studies, 2024)
The article studies the impacts of the pandemic caused by the COVID-19 virus on cultural festival organizations in Finland. Festivals have been institutionalized as network organizations, which presumes boundary work with partner organizations from different institutional fields. The organizational pattern of cultural festivals is studied qualitatively by applying institutional theory and particularly the perspective of hybridity due to the network pattern of festival organization.The institutionalization of cultural festivals promoted stability and guaranteed economic support during the pandemic, although the organizations had to run down most of their events. The small-scale impacts were the changes in the network structures and related reshaping of the programs.